A pilot study of a rapid assessment method to identify places for AIDS prevention in Cape Town, South Africa. (1st April 2002) - Weir, S S; Morroni, C; Coetzee, N; Spencer, J; Boerma, J T
Abstract : A multidisciplinary approach appears promising for focusing interventions. The PLACE method (priorities for local AIDS control efforts) identifies where prevention programmes can access sexual networks containing individuals with high rates of new partner acquisition and provides information about whether sexually transmitted disease (STD) or AIDS prevention programmes are in place at those sites. The method provides useful information at relatively low cost, regardless of the phase of the HIV or STD epidemic. For example, in the growth phase of an epidemic, information on where people with high rates of new partner acquisition meet new sexual partners could be used to inform targeted surveillance or screening programmes to catch early cases.